Increase Self-Regulated Learning of Junior High School Students with the Experiential Seamless Learning Model - Sri Catur Purnawati; Yatim Riyanto; Bachtiar Sjaiful Bachri; Hanandita Veda Saphira (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Study this to increase participants' self-regulated learning abilities and educate junior high school level through implementing the Experiential Seamless Learning model. Method: The research method used is the ADDIE development model proposed by Branch, involving 66 participants educated as subject research. Data was collected through a questionnaire to evaluate the eligibility product and test used to measure its effectiveness. Data analysis was done using a difference test (independent sample t-test). Results: The results of the study show that the Experiential Seamless Learning model, in a way, can significantly enhance participants' self-regulated learning education. Analysis indicates a significant difference​ between classes implementing this model and those using the learning method. The average value of self-regulated learning in classes using the Experiential Seamless Learning model is higher compared to class. Novelty: The novelty aspect of this study lies in the systematic integration between two learning models, experiential learning and seamless learning, which in previous studies were still applied separately. Another innovation of the Experiential Seamless Learning model is its use in improving self-regulated learning in the context of learning Indonesian at the junior high school level. The limitations of this study lie in the scope of the subject, which involved only two classes with a total of 66 students. In addition, the application of this model only covers seven of the ten dimensions of mobile seamless learning.